Avaliação da qualidade de um córrego urbano com relação às espécies metálicas e hidrocarbonetos policíclicos aromáticos (HPA) - Niño Camacho, Leidy Rocío (Universidade Federal de São Carlos, 2012)
Frequent use of urban waters for public supply has been increased, due to reduction of water resources suitable for human consumption. These waters are exposed to point and non-point sources of pollution, such as, atmospheric deposition, vehicle emissions and different types of waste thrown into streets and sidewalks. With storm water events, various toxics compounds are carried by surface run-off, reaching finally, into water bodies within the city. The goal of this research was to evaluate the presence of total mercury, polycyclic aromatic hydrocarbons (PAHs), heavy metals potentially toxic and acid volatile sulfide (AVS) in the hydrographic basin of Stream Barnabé. Searching environmental impact indicators on an aquatic system located at urban area of Indaiatuba, this water is captured to supply about 40.000 persons. Three points of stream were monitored, close to source, to water intake and to outfall. Water samples were collected monthly and sediments samples quarterly, between april/2010 and junho/2011. The results showed that the highest concentrations of mercury in water were observed during periods when rain interrupted the drought, due to runoff of water containing the material deposited for non-point sources in urban areas during the dry. The point next to water intake presented the highest concentrations of total-HPAs and AVS. We found that the maximums concentrations of metals were reported in setembro/2010 and junho/2011 samples and also setembro/2011 samples it found high concentrations of low molecular weight PHAs (naphthalene, acenaphthene, acenaphthylene and _etrogen) of source _etrogenico. These values were due to superficial water s flux with material deposited by nonpoint sources, accumulated during the dry season. Even though the results have shown normal impact indicators evaluated, it was denoted a vulnerability in this type of supply option, this requires an appropriate consideration in water management, such as interruption of supply, especially in times of heavy rainfall after periods of drought.
Keywords: Química analítica; Química ambiental; Metais; Hidrocarbonetos policíclicos aromáticos; Águas urbanas; Sedimentos; SVA-MES; Metal species; PAHs; Urban water; Sediment; AVS-SEM; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA